Developmental care for preterm infants: a scoping review of interventions, outcomes, and implementation contexts - Hastuti, Dwi; Anggorowati,; Zubaidah, Zubaidah (Frontiers in Pediatrics, 2026)
BackgroundPreterm infants face high risks of neurodevelopmental, physiological, and psychosocial challenges. Developmental care interventions have become essential strategies to improve infant outcomes and strengthen parental involvement in neonatal intensive care units.ObjectiveThis systematic review aimed to synthesize evidence on the effectiveness, implementation, and contextual adaptability of developmental care interventions for preterm infants.MethodsA systematic search of six databases was conducted for studies published between 2020 and 2025. Thirty-five studies met the inclusion criteria, including randomized controlled trials, quasi-experimental, cohort, and mixed-method designs. Interventions analyzed included Family Integrated Care (FICare), Kangaroo Mother Care (KMC), cue-based care, individualized developmental programs, and environmental modifications.ResultsFICare showed consistent benefits in breastfeeding, growth, neurodevelopment, and parental outcomes. KMC improved thermoregulation, cerebral perfusion, and behavioral responses. Cue-based and individualized care enhanced long-term cognitive and motor development, while environmental interventions yielded varied results. Contextual factors—such as parental literacy, infrastructure, and cultural norms—were key to implementation success. Evidence from LMICs emphasized the value of culturally adapted, digitally supported care models.ConclusionsDevelopmental care interventions significantly improve outcomes for preterm infants and families. Future research should focus on standardizing outcomes, ensuring long-term follow-up, and applying implementation frameworks to develop scalable, context-specific care models.